2020
DOI: 10.5005/jp-journals-10005-1857
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Effectiveness of Tell-Play-Do, Film Modeling and Use of Smartphone Dental Application in the Management of Child Behavior

Abstract: Aim To evaluate the effectiveness of three different behavioral modification techniques: tell-play-do (TPD), film modeling, and use of smartphone dental app in the management of child behavior. Settings and design Seventy-five children aged between 6 years and 9 years who were on their first dental visit were randomly divided into three groups. The study was conducted into two visits. Materials and methods First visit: group I—children watche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…54 Several studies conducted in Pakistan, Egypt, and India have also reported using smartphone applications to reduce dental anxiety levels. 22,30,51 Smartphones can be used to open game applications that are used to reduce anxiety. 22,51 This cross-sectional studies found that the presence or absence of parents did not affect the increase in positive behavior during visits.…”
Section: Alpha Generation Behavior Management In Dentistrymentioning
confidence: 99%
“…54 Several studies conducted in Pakistan, Egypt, and India have also reported using smartphone applications to reduce dental anxiety levels. 22,30,51 Smartphones can be used to open game applications that are used to reduce anxiety. 22,51 This cross-sectional studies found that the presence or absence of parents did not affect the increase in positive behavior during visits.…”
Section: Alpha Generation Behavior Management In Dentistrymentioning
confidence: 99%
“…A total of 20% (9/45) of the studies focused on knowledge, attitudes, and practice [26][27][28][29][30][31][32][33][34]. In total, 11% (5/45) of the studies were based on treatment outcome [35][36][37][38][39], and 9% (4/45) of the studies reported on the use of mobile apps in the management of dental anxiety [40][41][42][43]. Only 2% (1/45) of the studies were based on disease diagnosis [44], and 2% (1/45) of the studies were based on remote dental care services [45].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Similarly, 26% (6/23) of the studies reported significant improvement in gingival health measured via bleeding on probing [51,[53][54][55]57,59], and only 4% (1/23) of the studies reported a reduction in enamel caries [59]. Regarding dental anxiety management, 75% (3/4) of RCT studies reported a significant decrease in mean heart rate and lower image scale scores compared with the controls [41][42][43].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…However, in search of the literature, a few studies could be found on managing pediatric patients using the TPD technique (Kevadia et al, 2020). Therefore, this study aimed to assess the effectiveness of the tellplay-do technique compared to the tellshow-do technique in managing anxious children.…”
Section: Becausementioning
confidence: 99%
“…In the tell-play-do technique, children were asked to play with toys that imitate dental devices, such as a saliva ejector, a mouth mirror, dental probe, and air/ water syringe (Kevadia et al, 2020). A child's uncooperative behavior can hinder the effective administration of dental care.…”
mentioning
confidence: 99%